Identification of novel Single Nucleotide Polymorphisms (SNPs) associated with brown planthopper, Nilaparvata lugens (Stal.) resistance in rice (Oryza sativa L.) - Varma, N. R. G.; Mohan, Y. Chandra; Babu, T. Kiran; Singh, T. Virender Jeet; Ramakrishna, A.; Harikrishna, J.; Kumar, Aravind; Singh, Vikas Kumar; Singh, Uma Maheshwar; Kalia, Sanjay; Sinha, Pallavi; Krishna, T. S.; et al. (Horizon E-Publishing Group, 2025)
The brown planthopper (BPH) is one of the most predominant rice insect pests in Asia. Changes in the virulence pattern of BPHacross the regions and breakdown of resistance in many released resistant cultivars warrant identification of novel and diverse germplasm resources that can be deployed for developing new rice varieties with a broader genetic base. Accordingly, the field phenotypic screening was conducted over two years during kharif 2020 and 2021 using 300 rice genotypes (selected from 3 K subset of BPH panel) along with eight checks in an augmented block design to identify the BPH-resistant donor lines. Two rice genotypes viz., IRGC 126266 and IRGC 128206 exhibited consistent resistant reaction during both years. Mechanism of resistance studies (conducted duringrabi 2021-2022) revealed that, among the two promising germplasm, IRGC 126266 exhibited all the three mechanisms of resistance by recording lower honey dew excretion (72.5 mm2), lower nymphal survival rate (47.5 %), longer nymphal development period (17.20 days), lowest growth index (2.4) and took more days to wilt (27.2) compared to the susceptible check, TN1. Genome Wide Association Studies (GWAS) analysis was conducted in the 3K subset of BPH panel using four single locus models to identify the SNPs associated with BPH resistance. Significant SNPs were identified in proximity with several BPH resistance genes viz., Bph33(t), Bph13(t), Bph6, Bph34, Bph3, Bph4, Bph25, Bph29, Bph32, Bph28(t), Bph2, Bph26, Bph7, Bph9, Bph18(t) and Bph21(t). Candidate gene analysis study revealed that 9 Quantitative Trait Nucleotides (QTNs) associated with stress tolerance genes played a significant role in BPH resistance.